THE INTERNATIONAL LEGAL REVIEW OF THE MANAGEMENT OF OIL AND GAS IN INDONESIA - Khairunnisa, Nur Fitriani (Tadulako Law Review, 2016)
Abstract This research aims to determine the regulations of international law and the national law on the management of oil and gas in Indonesia. This research was conducted in several related Institutions in Jakarta, such as the Ministry of Energy and Mineral Resources, Directorate general of Oil and Gas, Ministry of Foreign Affairs and Pertamina Jakarta. This research conducted field research method, to find out the primary data through interviews with several resources who have competent research above objects, also used literature research method to find out the secondary data through the documents related to the object of research. The implementation of the cooperation contract adopting the system of the national sovereignty, in the implementation, each country has a different forms according the development of the contract system of oil and gas. Keywords: Contract, Oil and Gas in Indonesia